Diagnostic for the execution of research projects and its relation with improvement of learning the subject of Electrical Machines in students of the Faculty of Electrical and Electronic Engineering of the National University of Engineering in the academi - Cáceres C., Víctor (2017)
This research has a main goal to show that the Diagnostic for the execution of research projects is related with improvement of learning the subject of Electrical Machines in students of the Faculty of Electrical and Electronics Engineering of the National University of Engineering in the academic year 2016; sustained in note records of the students from the investigators members. Research is important, because applying educational strategies like the execution of guided Investigation, Projects and the execution of innovation Projects that contributes patenting, with participation of students and advisors and its regulation or order, and through the development of a Regulation of Organization and Functions; contributes in the best possible manner at the good professional education of the Faculty of Electrical and Electronic Engineering of the National University of Engineering. This research proves that it is necessary and important to put into practice the educational strategies mentioned above to improve teaching ‐ learning process quality of the subject of Electrical Machines, as well as improve the job training of the mentioned faculty´s students.